The Elusive Effects of Minimum Wages - Goldberger, Arthur S.; Lettau, Mike; Scholz, Karl; Staiger, Bob (Journal of Economic Literature, 1995)
The main theme of David Card and Alan Krueger's book, Myth and Measurement: The New Economics of the Minimum Wage, is that the data do not support the view that minimum wages reduce employment. The most important chapter considers data for the fast food industry, where it is suggested that recent minimum wage increases may actually have increased employment, contrary to the standard theorem that labor demand curves slope down. A more reasonable view of the evidence, in this book and in many other studies going back to 1915, is that the employment effects of minimum wages are small, and difficult to detect in the noisy data available.